Requested to extend the period for submission of completed CAR documents - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the request to extend the period for submission of completed CAR (Contractor's All Risk) documents of BRACU new campus project.